“Army of Mercy“ (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Women in Serbia started organizing themselves as early as the second half of the 19th century. The Society of Jewish Women was founded in 1874 and the Belgrade Society of Women was founded in 1875. The central aims of this society were humanitarian. Soon the members directed their activities towards medicine. In 1876, during the first Serbian-Ottoman War a hospital was founded by the members where the wounded were looked after. The society Princess Ljubica led by Milka Vulović was established in 1899. This society focused on helping the Serbian people in Old Serbia. The society Circle of Serbian Sisters was founded in 1903. Its founders were Nadežda Petrović and Delfa Ivanić. Apart from many humanitarian and educational initiatives and the constant struggle for women’s rights, one of the main objectives of these societies was to train its members for nursing. The first training course was started by the Belgrade Society of Women as early as 1875 and the second was started by the Circle of Serbian Sisters in 1906. Delfa Ivanić later wrote that ”It was a way for Serbian women to voluntarily complete their military service.” Through these courses the societies managed to mobilize ”an army of women” at the beginning of the Balkan Wars – army of mercy, as they were called at the time. Prior to the outbreak of war, women’s societies submitted to the Ministry of Defence a list of 1,500 trained nurses immediately available for the military ambulance.
Keywords: women’s societies; Belgrade Women’s Society; Princess Ljubica Society; The Circle of Serbian Sisters; volunteer nurses